The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1471-2180-10-245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of culture and qPCR for the detection of Pseudomonas aeruginosa in not chronically infected cystic fibrosis patients

Abstract: BackgroundPseudomonas aeruginosa is the major respiratory pathogen causing severe lung infections among CF patients, leading to high morbidity and mortality. Once infection is established, early antibiotic treatment is able to postpone the transition to chronic lung infection. In order to optimize the early detection, we compared the sensitivity of microbiological culture and quantitative PCR (qPCR) for the detection of P. aeruginosa in respiratory samples of not chronically infected CF patients.ResultsIn this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Regarding the sample type, i.e. sputum, cough swab, throat swab or nasopharyngeal aspirate, we found no significant linkage between the sample type and dissimilarity between qPCR and culture sensitivity [26], while Logan et al [24] and McCulloch et al [27] found proportionally more qPCR positive/culture negative sputum samples (resp. 6.1% and 23%) in comparison with qPCR positive/culture negative throat swabs and cough swabs (resp.…”
Section: Sensitivity Of the Qpcr Formatsmentioning
confidence: 87%
“…Regarding the sample type, i.e. sputum, cough swab, throat swab or nasopharyngeal aspirate, we found no significant linkage between the sample type and dissimilarity between qPCR and culture sensitivity [26], while Logan et al [24] and McCulloch et al [27] found proportionally more qPCR positive/culture negative sputum samples (resp. 6.1% and 23%) in comparison with qPCR positive/culture negative throat swabs and cough swabs (resp.…”
Section: Sensitivity Of the Qpcr Formatsmentioning
confidence: 87%
“…2007/503). Study was performed in accordance with approved national and international guidelines; written informed consent was obtained from all the patients > 18 years or from the parents and children older than 12 years, as previously reported [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…aeruginosa [1], and received the same antimicrobial treatment: Tazocin ® (Piperacillin/Tazobactam 4000mg/500mg) by intravenous administration during 15 days. Sputum samples were collected as previously reported [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…Our study also indicates the high potential of SF in the diagnosis of candidemia -we observed a signifi cantly higher detection rate of SF for C. albicans. [16,17,20,28,29]. A possible explanation for higher detection rate of P. aeruginosa is that in cases of bacteraemia, it is almost always isolated from the aerobic blood culture bottles only, thereby signifi cantly decreasing the likelihood of detection [30].…”
Section: Discussionmentioning
confidence: 99%